Empirical Evidence on Moral Contextualism - Jones, Larry A. (Review of religious research, 1978)
Analysis of survey responses from 1324 Methodist and Catholic laity and clergy shows that contextualism is an empirical reality. Liberal clergy are most contextualist. Contextualism is different from ambivalence and is not simply a repudiation of traditional prohibitions. Items eliciting contextualist responses are not symbolically central and appear to involve a specific application of a general rule.